Surface immobilized e-cadherin mimetic peptide regulates the adhesion and clustering of epithelial cells - Li, Jie; Russo, Jacopo Di; Hua, Ximeng; Chu, Zhiqin; Spatz, Joachim P.; Wei, Qiang (Advanced healthcare materials, 2019)
Cadherin mimetic peptides are widely used in synthetic biomaterials to mimic cell-cell adhesion in cell microniches. This mimicry regulates various cell behaviors. Although the interaction between immobilized cadherin and cells is investigated in numerous studies, the exact manner of functioning of cadherin mimetic peptides is yet to be fully understood. Cadherin mimetic peptides mimic only the critical amino acid sequence of cadherin and are not equal to these proteins in function. Compared to the cadherin proteins, mimetic peptides are more stable, easier to fabricate, and exhibit a precise chemical composition. In this study the E-cadherin mimetic peptide His-Ala-Val (HAV) on material surfaces is immobilized and epithelial cell adhesion and clustering are studied. The results suggest that immobilized HAV peptides specifically interact with E-cadherin on the cell membrane, resulting in an increased expression of E-cadherin and its downstream signaling protein β-catenin. This interaction relocates E-cadherin-based adhesion from the cell-cell interface to the cell-materials interface, which promotes cell adhesion via mechanosensing and initiates a transition in the cell cluster from a solid-like to a fluid-like state. The study presents an overview of the interactions between E-cadherin mimetic peptide and epithelial cells to aid in the design of novel biomaterials.
Gesehen am 27.03.2020